2016
DOI: 10.15835/nsb.8.2.9793
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Foliar Zinc Application on Yield, Physiological Traits and Seed Vigor of Two Soybean Cultivars under Water Deficit

Abstract: In order to study the effect of water deficit stress and zinc foliar application on yield, physiological traits and also on seed vigor and seedling emergence percentage in two soybean cultivars, an experiment was conducted as randomized complete block arrangement in split factorial design with three replications. The main factor was drought stress in three levels of optimal irrigation, withholding irrigation from vegetative growth stage and withholding irrigation from flowering stage; subordinate factors were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 24 publications
1
3
0
Order By: Relevance
“…The well-watered plants measured significantly higher stem diameters (2.85 cm) than the mild and severe drought stress by 14.03 and 28.7%, respectively. Our results are in agreement with those found by Karami et al (2016) for soybean cultivars [Glycine max (L.) Merr. ], which indicated that drought stress reduced plant growth, plant height and stem diameter due to disturbance in photosynthesis and low carbohydrate production.…”
Section: Plant Height and Stem Diametersupporting
confidence: 93%
“…The well-watered plants measured significantly higher stem diameters (2.85 cm) than the mild and severe drought stress by 14.03 and 28.7%, respectively. Our results are in agreement with those found by Karami et al (2016) for soybean cultivars [Glycine max (L.) Merr. ], which indicated that drought stress reduced plant growth, plant height and stem diameter due to disturbance in photosynthesis and low carbohydrate production.…”
Section: Plant Height and Stem Diametersupporting
confidence: 93%
“…Our results showed that the applying of zinc in beans at low doses increased the proline and at higher doses, proline decreased significantly. (36) reported a decrease in the amount of soybean leaf proline under different levels of irrigation by using the Zn and reported that receiving Zn via leaf in plant, reduced a large portion of glutamate that was involved in chlorophyll biosynthesis. This compound plays a role in the proline biosynthesis pathway.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Ceritoglu and Erman ( 2020 ) reported that drought stress at vegetative and reproductive stages resulted in approximately 15% and 30% yield reduction respectively, while drought stress during vegetative and flowering periods reduce grain quality and quantity of cowpea genotypes. It is therefore important to study the pod and seed chemical composition of cowpea as influenced by environmental conditions (such as drought stress), stage of growth and cultivar (Karami et al 2016 ).…”
Section: Introductionmentioning
confidence: 99%